The Effect of Dividend Announcement on Stock Prices in the Malaysian Stock Market - Soh, Hong Jiu (2010)
This study aims to examine the impact of dividend announcement on the Malaysian stock market. Miller and Modigliani Theorem explains that a hype will be created among investors whenever there is an increase in dividend payments as it conveys positive signal whereas a decrease in dividend payments will transmit negative signal. Therefore, investors will change their views towards the firm‟s future value when a firm‟s dividend policy is changed. This idea has also been theorized in Dividend Signaling Theory by Miller and Modigliani (1961). This study uses event study methodology to address how fast the stock prices react to the information announcement under the assumption of the semi-strong form of efficient market hypothesis. Firstly, the analysis is based on a sample of 50 companies listed on the Bursa Malaysia (initially was called Kuala Lumpur Stock Exchange, KLSE) over a period of 5 years, from January 2001 to December 2005. The study reveals that there are positive and statistically significant reactions for dividend increase, dividend decrease and dividend unchanged announcements on day +1 although the stock prices do not respond correspondingly during the announcement day. Subsequently, the study examines the stock prices reaction to dividend announcements from year 2000 to year 2005 without categorizing the samples into the classifications of dividend „increasing‟, „decreasing‟ and „no change‟. There is only one statistically positive standardized abnormal return on the announcement day among the six years, whereas there are four years showing statistically positive standardized abnormal return on day +1, which is consistent with the previous findings. Hence, this study sheds new light on issue of corporate dividend behavior to the investors and shareholders.